Dissociable effects of psychopathic traits on cortical and subcortical visual pathways during facial emotion processing: An ERP study on the N170 - Pedro Almeida (2014)
This study examined the relation between psychopathic traits and the brain response to facial emotion by analyzing the N170 component of the ERP. Fifty-four healthy participants were assessed for psychopathic traits and exposed to images of emotional and neutral faces with varying spatial frequency content. The N170 was modulated by the emotional expressions, irrespective of psychopathic traits. Fearless dominance was associated with a reduced N170, driven by the low spatial frequency components of the stimuli, and dependent on the tectopulvinar visual pathway. Conversely, coldheartedness was related to overall enhanced N170, suggesting mediation by geniculostriate processing. Results suggest that different dimensions of psychopathy are related to distinct facial emotion processing mechanisms and support the existence of both amygdala deficits and compensatory engagement of cortical structures for emotional processing in psychopathy.